2013
DOI: 10.1177/0300985813498779
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Evaluation of the Utility of Transcriptional and Urinary Kidney Injury Biomarkers for the Prediction of Aristolochic Acid–Induced Renal Injury in Male Rats

Abstract: The predictive value of different urinary and transcriptional biomarkers was evaluated in a proof-of-principle toxicology study in rats using aristolochic acid (AA), a known nephrotoxic agent. Male Wistar rats were orally dosed with 0.1, 1, or 10 mg/kg for 12 days. Urine was collected on days 1, 5, and 12 over 24 hours. Gene expression analysis was also conducted using quantitative realtime polymerase chain reaction and Illumina whole-genome chips. Protein biomarkers (Kim-1, Timp-1, vascular endothelial growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Osteopontin can be used as a biomarker for ovarian cancer ( Rainczuk et al, 2013 ), kidney stones ( Bautista et al, 1996 ), bladder cancer ( Yang et al, 2011 ) and drug-induced kidney injury ( Phillips et al, 2016 ). Calbindin can serve as a biomarker for distal nephron segment injuries ( Iida et al, 2014 ), nephrotoxicity ( Hoffmann et al, 2010 ), acute kidney injury ( Togashi et al, 2012 ) and drug-induced renal injury ( Fuchs et al, 2014 ). Complement C3 can act as a biomarker of IgA nephropathy ( Liu et al, 2014 ) and glomerulonephritis ( Cumming et al, 1976 ).…”
Section: Resultsmentioning
confidence: 99%
“…Osteopontin can be used as a biomarker for ovarian cancer ( Rainczuk et al, 2013 ), kidney stones ( Bautista et al, 1996 ), bladder cancer ( Yang et al, 2011 ) and drug-induced kidney injury ( Phillips et al, 2016 ). Calbindin can serve as a biomarker for distal nephron segment injuries ( Iida et al, 2014 ), nephrotoxicity ( Hoffmann et al, 2010 ), acute kidney injury ( Togashi et al, 2012 ) and drug-induced renal injury ( Fuchs et al, 2014 ). Complement C3 can act as a biomarker of IgA nephropathy ( Liu et al, 2014 ) and glomerulonephritis ( Cumming et al, 1976 ).…”
Section: Resultsmentioning
confidence: 99%
“…NGAL is also over-expressed in human cancers [45]. In terms of AAI treatment, previous in vivo work demonstrated that Ngal can be used as a biomarker of exposure [46]. Moreover, LCN2 was upregulated in AAI-exposed TP53(+/+) and TP53(-/-) HCT116 cells [28].…”
Section: Discussionmentioning
confidence: 96%
“…Osteopontin can be used as a biomarker for ovarian cancer (Rainczuk et al 2013), kidney stones (Bautista et al 1996), bladder cancer (Yang et al 2011) and drug-induced kidney injury (Phillips et al 2016). Calbindin can serve as a biomarker for distal nephron segment injuries (Iida et al 2014), nephrotoxicity (Hoffmann et al 2010), acute kidney injury (Togashi et al 2012)and drug-induced renal injury (Fuchs et al 2014).…”
Section: Differential Proteins As Candidate Biomarkers and Their Humamentioning
confidence: 99%